Students’ Semantic and Pragmatic Challenges in Comprehending Basic Legal English Vocabulary of Law Students in University of Tjut Nyak Dhien Medan - Adlina, Min; Halawa, Agusman (International Journal Linguistics of Sumatra and Malay, 2025)
Legal English contains expressions whose meanings often diverge from everyday usage, which makes them challenging for learners who approach the language without sufficient background in legal contexts. This qualitative study explores how Indonesian readers interpret basic legal vocabulary and identifies patterns of misunderstanding from both semantic and pragmatic perspectives. The data reveal three recurring concerns: difficulties with polysemous terms, misinterpretation of context-bound legal expressions, and uncertainty when encountering formulaic or Latin-derived phrases. These findings echo the latest discussions in legal linguistics and applied semantics (Biel, 2020; Trosborg, 2023; Williams, 2022). A notable factor contributing to these issues is the learners’ limited exposure to authentic legal texts. The article recommends strengthening context-sensitive vocabulary instruction and providing corpus-based learning resources to build more accurate semantic and pragmatic awareness.